National Health and Nutrition Examination Survey II, 1976-1980: Physician Examination, Ages 6 Months-74 Years ([Verlag nicht ermittelbar], 1988)
The NHANES II Physician Examination data collection contains two parts of the extensive data available from NHANES II: demographic information obtained during the household interview, and the results of the physician's examination. The demographic data include information on the type of residence and housing, composition of the household, vehicles, languages spoken, income sources and amounts, food stamps and commodity foods, employment, age, race and national ancestry, sex, education, marital status, veteran status, and region of country. The physical examination data include 1)measurements of systolic and diastolic blood pressure, 2)examination of head, eyes, ears, nose, and throat, 3)thyroid and chest evaluations, 4)heart, pulse, kidney and abdominal evaluations, 5)examinations of joints, 6)musculoskeletal evaluations, and 7)limited neurological and skin evaluation. The data also include a summary of diagnostic impressions coded by the standard International Classification of Diseases, Adapted (ICDA) codes.